PTH-011 Endoscopic mucosal resection (emr) vs. endoscopic submucosal dissection (esd)/hybrid in the management of large colorectal polyps: experience from a tertiary centre. (17th June 2017) - Lambert, J; Scott, J; Crooks, B; Kurrimboccus, S; Prasad, N; Hammonds, R; George, R
Abstract : Introduction: In tertiary centres both EMR and ESD sometimes in combination with hybrid techniques are used in the treatment of polpys>20 mm. EMR allows for removal of polyps confined to the mucosa often in a piecemeal fashion while ESD aims for enbloc resection for lesions extending into the submucosa. The most serious complications include bleeding and perforation. Over a 3 year period at a tertiary centre we aimed to assess complication and recurrence rates between these two modalities. Method: Data was collected retrospectively collected over a 3 year period. All EMR/ESD were performed by three dedicated consultant endoscopists with over 10 years experience in performing level III and IV endoscopic resection. The endoscopy Unisoft database was interrogated to select all patients having EMR/ESD including screen-detected lesions. Lesions<20 mm were excluded and all patients were assessed for length of hospital stay (LOS), recurrence and complication rates. The first follow-up endoscopic examination was performed at 3–6 months after initial endoscopic resection, and the second at 12–14 months post-EpMR Results: 128 polyps were removed endoscopically from 125 patients (80 males) 64%. Mean age was 70 and mean polyp size 38 mm (range 20–101 mm). For low-grade dysplatic lesions histology confirmed 83 (64%) tubulo-villous adenomas (TVA) and 21 (16%) Tubulo-adenomas (TA). There were 11 (8.5%) adenocarcinomas, 7 (5.4%) and high-grade dysplastic lesions. All adenocarcinomas were eventually referred for surgical management. One large high-grade dysplastic lesion was referred for Trans-anal microscopic surgery (TEMS) after submucosal fibrosis and bleeding encountered during ESD. There were 6 (4.6%) inflammatory/hyperplastic lesions. Procedural bleeding was encountered in six patients, one patient had delayed bleeding. One patient had post-polypectomy pain syndrome. There were no perforations. No difference in complication rates was found between EMR and ESD. 12 month recurrence rate was 15/113 (13%). This was related to increasing size of polyps. All recurrences were managed endoscopically. LOS was between 0–24 hours in over 97% of patients. Conclusion: In high volume centres EMR/ESD is safe with low complication and recurrence rates. Disclosure of Interest: None Declared